Unravelling US maternal mortality through critical discourse analysis. (October 2019) - Allen, Rebecca; Sovik Benedetti, Mary
Objectives: Given that pregnancy health information seeking is common and considered impactful on health outcomes, the potential lack of fair and clear information within media may be an impediment towards women developing their own agency and working towards the transformation and betterment of their own outcomes. Setting: The USA has the worst maternal mortality rate of any developed country. Women's opinions are shaped and informed by public media and discourse; therefore, a critical look at how public media texts support women's agency is of significance. Method: Reducing maternal mortality requires more than just effective health interventions. This paper uses critical discourse analysis to examine two samples of widely viewed public discourse around the issue of US maternal mortality and reveals the murky and polarised dialogue contained in each. Results: The two samples may be representative of a larger lack of clarity in US discourse about maternal mortality, a body of discourse which – to the detriment of women's maternal morbidity and mortality outcomes – subtly but powerfully either declines to admit mistakes or uses polarising, overly simplified language. Conclusion: Recognising the polarised dialogue surrounding maternal mortality and working towards a more reasoned discussion of the issue at hand may promote women's advocacy and provide potentially better outcomes.